Peranan Komisi Pemilihan Umum Daerah Dalam Penyelenggaraan Pemilihan Kepala Daerah Langsung Dalam Meningkatkan Partisipasi Masyarakat Di Kabupaten Halmahera Timur - Ngongare, Frangky; Pangkey, Masje Silija; Tampongangoy, Deysi Livi (Sam Ratulangi University, 2015)
ABSTRACT : This research aims to know the role of the Regional Electoral Commission in organizing theelection head East halmahera Regency area. And to know how the electoral region of East HalmaheraRegency in increasing participation in the election of the head of the region. Electoral Commission is chosenand defined by law the inaugural election, where at the beginning of its formation, the Electoral Commissionis the agency that consists of people who are nonpartisan and most of the colleges and non-governmentalpeople. The regional Election Commission is subordinate to the Central Electoral Commission to organize theelections are tiered.The research methods used in this research is qualitative, descriptive methods, using primary data collectiontechniques. While the primary informants amounted to 3 people, yaitu: 1. Technical Defisi technical electionsubsection coconut and public relations Head of Sub-Division 3 programs and data and additional informants,those who can provide information although not directly involved in social interaction that is thorough, peoplenamely , academic, and religious figures.From the results of the examination can be conclude that the performance of the Regional ElectoralCommission East Halmahera in increasing community participation in elections of the head of the area canalready say good, because in this case there is the occurrence of an increasing number of voters being 70%, inaddition also many promotional activities and socialization activities performed by the Regional ElectoralCommission in order to attract sympathetic community. Reference from the conclusions above, in order thatthe Commission recommend to the regional elections of East Halmahera can be more enterprising againsocialisation in order public participation in choosing the higher.Key words: Regional Electoral Commission and community participation